A biomechanical model for swimming performance - Francis, P. R.; Dean, N. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
This study is an attempt to develop a mathematical model involving those factors that govern maximal performance levels in freestyle swimming. Levels of athletic performance are determined by the interaction of three factors that govern all functions of the human organism. These factors may be classified as the mechanical, the physiological, and the psychological. It is logical to assume that any complete investigation of athletic performance must account for the effects of all three of these factors. At the present time relatively sophisticated tools are available for the measurement of mechanical and physiological variables in the swimmer, but instruments designed to evaluate appropriate psychological variables are of questionable validity. Therefore, the present first approximation model incorporates both mechanical and physiological variables, while no attempt has been made to examine the influence of psychological factors. In an attempt to control the psychological variables, however, the present model was validated using world recora performances for men and women swimmers. It was assumed that world record performances would be indicative of near maximal levels of motivation for the performers.